Analisis Migrasi Di Kabupaten Pelalawan Tahun 2010 - 2021 - Saputra, Muhammad Sahal dony (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Timor, 2023)
Migration is an activity of moving people from one area to another with the aim of getting a better life. An urgent situation makes a person to make a decision in migrating, where individuals move to big cities is the hope to get a job and earn a higher income than that obtained in the area of ​​origin. This study aims to see the relationship between per capita income, district minimum wages, investment on the number of in-migration in Pelalawan District. The type of research used in this research is descriptive quantitative research. The type of research used in this study is descriptive quantitative research including secondary data for 2010 - 2021 taken from the Pelalawan Regency BPS, the PelalawanRegency Population and Civil Registration Office, and the Riau Province One Stop Investment and Integrated Service Office. Technical analysis used in this study is multiple linear regression analysis. Based on the results of this study, the regression coefficient value of the per capita income variable was -0.053598 with a significant level of 0.97. It can be concluded that the per capita income variable has a negative and insignificant effect on the migration variable. For the wage variable the value of the regression coefficient is - 1.426208 with a significant level of 0.04 it can be concluded that wages have a negative and significant effect on the migration variable. The value of the investment variable regression coefficient is -2.83E-05 with a significant level of 0.02. It can be concluded that the investment variable has a negative and significant effect on the migration variable in Pelalawan Regency in 2010-2021.